FIGURATIVE MEANING IN ALANI HAPOGOSAN MOVIE - Wantika Br Dabutar and Sumarsih (LINGUISTICA, 2017)
This study deals with the Figurative Meaning in Alani Hapogosan Movie. The objectives of the study are to describe the types of figurative language used in Alani Hapogosan Movie, the dominant type of the figurative language and the cultural values of the movie itself. This study was conducted by descriptive qualitative method. The data were collected from the Alani Hapogosan by transcribing them. In analyzing the data, there are 4 types of figurative language were used. The most dominant used is Metaphor 25 (44,64%), the second is Idioms 18 (32,14%), the third is Proverbs 11 (19,64%), the last is Metonymy 2 (3,57%) and there was not Irony occured in Alani Hapogosan movie. There were 8 cultural values that occured in the movie: Kinship (Kekerabatan), Religion (Religi), Wealth (Hamoraon), Honor (Hasangapon), Progress (Hamajuon), Law (Hukum), Guardianship (Pangayoman), Conflict (Konflik). And there was a cultural values that didn’t occur in Alani Hapogosan movie. It is Have Many Children (Hagabeon).